FAKTOR YANG MEMPENGARUHI KINERJA GURU BIMBINGAN DAN KONSELING DALAM PUBLIKASI ILMIAH DI SMP KABUPATEN PEKALONGAN - Sudibyo, Hanung (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2019)
Scientific publications in this case are compiling research actions on guidance and counseling and publishing the results of research into journals. The problem in this study is that the guidance and counseling teachers at Pekalongan District Secondary School experienced a decline in performance in preparing research studies on guidance and counseling as well as publishing articles in journals. The purpose of the research is to find out what factors influence the performance of teacher guidance and counseling in scientific publications. This research method uses qualitative research. The data collection method uses interviews and document studies. The results of the study are factors that influence the performance of teacher guidance and counseling in scientific publications including leadership, motivation, competence, and training. Previously, the training in arranging guidance and counseling action research and article publication had been carried out several times and was proven to be able to improve the professional competence of teacher guidance and counseling. This was accomplished, one of which was the support of leadership factors from the central policy, elements of the education agency, principals and organizations as well as teacher motivation. However, when the support of the leadership factor and the teacher's motivation factor decreased, the competence and training in arranging research and counseling actions as well as the publication of articles became decreased so that the teacher's guidance and counseling performance became low.